TEACHERS’ PERCEPTIONS TOWARDS TEACHING WRITING USING WORD GAMES; THE CASE STUDY OF JUNIOR HIGH SCHOOLS IN SEMARANG, CENTRAL JAVA, INDONESIA - Dias Andris Susanto; Maria Yosephine (Universitas PGRI Semarang, 2017)
This was a descriptive qualitative study which was done in 2017 at junior high schools in Semarang Central Java, Indonesia. This study focused on the teachers’ perception and teaching writing using word games. According to Chastain (1988)